2023
DOI: 10.1097/cp9.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the effects of fine and coarse particulate air pollution on the onset of stable and unstable angina: a case-crossover study in 305 Chinese cities

Abstract: Background and purpose: Associations between fine and coarse particulate matters (i.e., PM2.5 and PM2.5–10, respectively) and the onset of angina have rarely been investigated. We aimed to systematically explore the impacts of PM2.5 as well as PM2.5–10 on the onset of stable and unstable angina at the hourly timescale. Methods: We performed a time-stratified case-crossover study among 995,734 angina patients from 1,655 hospitals in 305 Chinese cities fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The study found that exposure to agricultural PM 2.5 was associated with an increased risk of acute MI, highlighting the need for more research on estimating the adverse health effects of different air pollution sources. The study conducted by Jiang et al explored the impacts of PM 2.5 and PM 2.5-10 on the onset of stable and unstable angina at an hourly temporal resolution, adjusting for key confounders [10] . They suggest that life-threatening cardiovascular disease risk from transient exposure to air pollution must be considered by healthcare professionals including cardiologists and patient caregivers to avoid negative cardiorespiratory outcomes.…”
Section: Air Pollution and Cardiovascular Heath In A Changing Climatementioning
confidence: 99%
See 1 more Smart Citation
“…The study found that exposure to agricultural PM 2.5 was associated with an increased risk of acute MI, highlighting the need for more research on estimating the adverse health effects of different air pollution sources. The study conducted by Jiang et al explored the impacts of PM 2.5 and PM 2.5-10 on the onset of stable and unstable angina at an hourly temporal resolution, adjusting for key confounders [10] . They suggest that life-threatening cardiovascular disease risk from transient exposure to air pollution must be considered by healthcare professionals including cardiologists and patient caregivers to avoid negative cardiorespiratory outcomes.…”
Section: Air Pollution and Cardiovascular Heath In A Changing Climatementioning
confidence: 99%
“…The study conducted by Jiang et al . explored the impacts of PM 2.5 and PM 2.5–10 on the onset of stable and unstable angina at an hourly temporal resolution, adjusting for key confounders [10] . They suggest that life-threatening cardiovascular disease risk from transient exposure to air pollution must be considered by healthcare professionals including cardiologists and patient caregivers to avoid negative cardiorespiratory outcomes.…”
mentioning
confidence: 99%